(untitled) (Bioscience Journal, 2016)
Licuri (Syagrus coronata (Mart.) Becc.) is an ornamental palm tree native of Brazil with great economic potential, because it provides raw material for manufacturing a wide range of products. The objective of this study was to assess the morphology of the fruits, diaspores, seeds, seedlings, and saplings of Syagrus coronata. The study was performed at the Laboratory of Seed Analysis (LSA) of the Federal Rural University of Pernambuco/Academic Unit of Garanhuns-PE, by using licuri fruits collected from the rural area of Caetés-PE. It was evaluated fruit morphology, diaspores, seeds, seedlings and saplings. Germination, in the form of cotyledon petiole emergence, began 15 days after sowing, is hypogeal, cryptocotylar, and remote tubular. It is slow and uneven, extending up to 60 days after the first eophyll appears. The saplings have alternate, pinnate, glabrous, entire leaves with parallel venation and sheath invagination. The primary roots persistent, the secondary roots arise from the stem root node in the primary root, and lateral roots only fasciculate was evidenced when the change was 300 days, and must remain in the nursery for at least 360 days after germination before taking it to the field, due to the slow development of this species.